“Calidad del servicio y su incidencia en la satisfacción del cliente de la cooperativa de ahorro y crédito San Antonio ltda. Los ríos, año 2022.” - Valero Morán, Keyla Janeth (2024)
This research proposes to analyze the relationship between the quality of the service provided by the Cooperativa de Ahorro y Crédito San Antonio Ltda. and customer satisfaction in the year 2022. In the competitive context of financial institutions, understanding how service quality affects the customer experience becomes essential for the success and sustainability of credit unions. The methodology used includes the collection of quantitative data through customer surveys and qualitative data through interviews with cooperative staff. Statistical tools are used to analyze the relationship between service quality indicators and customer satisfaction levels. Preliminary results suggest that there is a direct relationship between the quality of the service provided by the San Antonio Cooperative and customer satisfaction. Specific areas for improvement are identified, such as efficiency in response times and clarity in communication. This study offers specific recommendations to improve service quality, including implementing ongoing training for staff, optimizing processes, and improving internal and external communication. Regarding potential contributions, the research contributes to knowledge about service quality in cooperative financial institutions and provides a basis for making strategic decisions aimed at continuous improvement.